Konsep Inovasi Strategi Pendidikan di Institusi Pendidikan Kedokteran - Yoyo Suhoyo (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2012)
Innovation in medical education is essentially a reaction towards various demands and changes in the medical education institutions environment. The innovation of educational strategy is a part of the effort. Innovation in medical education should consider the feasibility level, resources needed, time and duration of implementation, scale and degree, that failure can occur, obstacles faced and the pattern of innovation that will be done. Considering the current condition of medical education institutions that are known through self-evaluation and strategic plan, and a growing trend in medical education at this time, severalinnovation can be proposed. SPICES approach can be taken as a guide in designing innovation in medical education.